Examining the gender digital divide: A case study from rural Kenya - Ferguson, Nathaniel; Seymour, Greg; Azzarri, Carlo (International Food Policy Research Institute, 2023)
Worldwide, cell phones are used by 5.4 billion people. They are becoming increasingly prevalent in the rural areas of low- and middle-income countries (LMICs), providing smallholder farmers with access to agricultural markets. If they reduce information asymmetries between women and men farmers, they can also contribute to closing the gender gap in agricultural productivity. So far, however, digital innovations have had limited success in transforming agricultural systems. This may be due, in part, to the gender gap in cell-phone use. Rural women in LMICs—particularly those with low incomes, low literacy levels, or disabilities—are less likely than rural men to have access to cell phones, the Internet, digital currency, or other digital services. This policy note summarizes research intended to shed light on the impact of cell-phone ownership and use on the gender gap in agricultural productivity in LMICs.